Analysis of Specific Water Consumption Based on Water Discharge Case Study of Batang Agam Hydroelectric Power Plant - Antonius Rajagukguk; Edy Ervianto; Firdaus Firdaus; Anjelina Ifelia Putri (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2023)
Renewable energy has an important role today, one of which is hydroelectric power plants which use water as the main resource. So the amount of water is very important for producing every 1 kWh of electricity, this is called specific water consumption. Each hydropower plant has different SWC standards. The research was carried out to determine the SWC value and generator efficiency at the Batang Agam Hydroelectric Power Plant in the period April 2022 to April 2023. The research method was carried out by observing and collecting the required data such as inflow, outflow and daily electrical energy distribution data. Calculate water volume, hydraulic energy and specific water consumption. The research results show that the swc is in the range of 3 -4 m3/kWh, which means this value is below the standard swc value for the Batang Agam Hydroelectric Power Plant, namely 4,808 m3/kWh. This is caused by the unstable condition of the water flow flowing from the river to the Batang Agam Hydroelectric Power Plant which is influenced by rainfall. And based on the electrical energy generated with the distributed electrical energy, the efficiency of the Batang Agam Hydroelectric Power Plant for one year is 71.66%.